Introduzione (Doctor Virtualis, 2022)
Introduction to the issue for Massimo Campanini"This issue is intended as a tribute to Massimo Campanini's ties with Milan, and in particular with Milanese scholars of the History of Medieval Philosophy; it is intended as a thank you for the contribution he has made to the journal, forcing us to confront another point of view, another narrative of history and historical and philosophical categories that are different but not alien to those of the Latin-Western world, enriching our outlook towards a Mediterranean and not exclusively Eurocentric perspective."
Keywords: Islamic Studies; History of Medieval Philosophy; Qur’ān; Politics